Durable pressure filtration membranes based on polyaniline–polyimide P84 blends. (27th April 2018) - Yusoff, Izzati Izni; Rohani, Rosiah; Khairul Zaman, Nadiah; Junaidi, Mohd Usman Mohd; Mohammad, Abdul Wahab; Zainal, Zamardina
Abstract : A pressure filtration membrane from conducting polymer polyaniline (PANI) is known to possess low mechanical strength and thermal stability. Therefore, it is believed that the properties of the membrane can be enhanced by blending PANI with a conventional polymer like polyimide (PI), which possesses high mechanical strength and thermal stability. A thermal analysis revealed that polymer chain of blend membranes started to break beyond the melting temperature of pure PANI membrane indicating that the addition of PI hindered the degradation of PANI and thus slowed down the decomposition process. Mechanical tests further showed that PANI/PI membrane had a tensile strength that was 60% higher than pure PANI membrane. Furthermore, the surface hydrophilicity and negativity of the blend membrane increased as it was doped in acid, thereby reflecting the exploitation of advantages of both polymers. Rejection at various molecular ranges of PEGs showed that PANI/PI membrane was initially in the ultrafiltration (UF) range, but later fell into the nanofiltration (NF) range when an acid dopant was introduced to the membrane. According to the long‐term filtration performance, the PANI/PI membrane was able to sustain a rejection of up to 99% in Congo red solution with just a slight reduction in flux. POLYM. ENG. SCI., 59:E82–E92, 2019. © 2018 Society of Plastics Engineers